2018
DOI: 10.21767/1791-809x.1000569
|View full text |Cite
|
Sign up to set email alerts
|

From Man to Father: Norwegian First-Time Fathers’ Experience of the Transition to Fatherhood

Abstract: Objective: To explore how men experience becoming a father for the first time and how they perceive their role during their partner's pregnancy, childbirth and the early period with a newborn child. Methods:The study had a qualitative design. Nine individual interviews were conducted with first-time fathers. Qualitative content analysis was used to interpret the data material.Results: The men's ages were from 25 to 45 years. They were all Norwegian, seven were cohabitants, and two were married. Four categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(34 reference statements)
0
2
0
3
Order By: Relevance
“…These have been called "reality boosters" (Jordan, 1990) or "body-mediated moments" (Draper, 2003). Men included these aspects in their accounts, describing how they helped them realize that the child was real and decreased the feeling of unreality, which was also described in previous studies (Chin et al, 2011;Solberg & Glavin, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…These have been called "reality boosters" (Jordan, 1990) or "body-mediated moments" (Draper, 2003). Men included these aspects in their accounts, describing how they helped them realize that the child was real and decreased the feeling of unreality, which was also described in previous studies (Chin et al, 2011;Solberg & Glavin, 2018).…”
Section: Discussionmentioning
confidence: 93%
“… 66 67 A review article concluded that mindful meditation could be taught to parents and was effective in improving self-regulation among those experiencing chronic stress. 68 A Norwegian study 69 reported that fathers’ positive engagement with children was dependent on a sense of mastery.…”
Section: Discussionmentioning
confidence: 99%
“…Masa transisi digambarkan sebagai periode kurangnya rasa percaya diri, kekurangan waktu istirahat serta memiliki tekanan emosional. Ayah merasa sangat sulit untuk membicarakan kesehatan mentalnya bahkan dengan pasangannya sendiri, terutama jika pasangannya juga mengalami gangguan kesehatan mental (Solberg and Glavin, 2018).…”
Section: Depresi Pasca Postpartumunclassified
“…Faktor ekonomi menyebabkan ayah bekerja lebih lama dan menyebabkan masalah psikologis karena keinginan untuk memastikan ketersediaan dan keamanan keuangan keluarga (Solberg and Glavin, 2018). Memiliki bayi berarti mengubah gaya hidup dan memiliki pengeluaran tambahan (Baldwin et al, 2019).…”
Section: Faktor Ekonomiunclassified